The Wage Returns to On-the-Job Training: Evidence from Matched Employer-Employee Data - Rita K. Almeida; Marta Lince de Faria (Institute for the Study of Labor (IZA), 2014)
Skills shortages and skill mismatch are a pressing concern for policymakers in several developing countries, and in East Asia specifically. Providing on-the-job training can be an effective policy tool to shape the skills of the existent workforce to the specific needs of the firms. This paper explores a unique data set of matched employer-employee data for Malaysia and Thailand to estimate the wage return to on-the-job training in these two countries. Exploring propensity score matching estimates, we show that the average wage returns to on-the-job training are 7.7% for Malaysia and 4.5% for Thailand. Furthermore, we find evidence that the wage returns to on-the-job training are higher for males than for females in Malaysia and that, for both countries, returns are higher for workers with at least secondary education.
Keywords: J24; J30; 330; matched employer-employee data; wages; on-the-job training